Risk Factors for Surgical Site Infections in Pediatric General Surgery: A Case–Control Study - Almogbel, Gassan T.; Altokhais, Tariq I.; Alhothali, Abdulaziz; Aljasser, Abdulaziz Sami; Al-Qahtani, Khalid M.; Arab, Sadiq F.; Alsweirki, Helmi M. H.; Albassam, Abdulrahman (Journal of Pediatric Infectious Diseases, 2021)
Objective Despite being the most common postoperative complication and having associated morbidity and mortality that increase health care costs, surgical site infection (SSI) has not received adequate attention and deserves further study. Previous reports in children were limited to SSI in certain populations. We conducted this retrospective case–control study to determine the incidence and possible risk factors for SSI following pediatric general surgical procedures.Methods This was a retrospective case–control matched cohort study of all patients aged 0 to 14 years who underwent pediatric general surgical procedures between June 2015 and July 2018. The electronic medical records were searched for a diagnosis of SSI. Control subjects were randomly selected at a 4:1 ratio from patients who underwent identical procedures. Multiple risk factors were evaluated by bivariate analysis and multivariable conditional logistic regression.Results A total of 1,520 patients underwent a general pediatric procedure during the study period, and of these, 47 (3.09%) developed SSIs. A bivariate analysis showed that patients with SSIs were younger, were admitted to the neonatal intensive care unit/pediatric intensive care unit (NICU/PICU) preoperatively, were more severely ill as measured by the ASA classification, underwent multiple procedures, had more surgical complications, and were transferred to the NICU/PICU postoperatively. A multivariate analysis identified four independent predictors of SSI: age, preoperative NICU/PICU admission, number of procedures, and ASA classification.Conclusion Younger children with preoperative admission to the NICU/PICU, those who underwent multiple procedures and those who were severely ill as measured by their ASA classification were significantly more likely to develop SSIs.
Keywords: surgical site infection; pediatric general surgery; incidence; risk factors